Making Women Human: Unveiling the Contribution of Women to the Universal Declaration of Human Rights - Abdulrahim P. Vijapur, (Al-Qanṭara, 2024)
The UDHR was adopted 75 years ago, on 10 December 1948. There are many myths surrounding the adoption of this historic and revolutionary document by the international community. Three of these myths are: Rene Cassin is the father of the UDHR; it is representing only Western or imperialist values and the male delegates from the Western countries played a dominant role in drafting it. The analysis in the paper dispels these myths. It argues that the UDHR is not authored by a single person. Its authorship is composite. It is the most translated and cited document in the world. It does not represent only the Western values; communist States, Muslim states and many small States have also made their seminal contributions in its drafting. The main focus of the paper is to document and analyse the role of women delegates, comprising only 3 per cent of all delegates participating in the drafting of the UN Charter and the UDHR, mostly from the Global South, in lobbying for including the provisions of ‘gender equality’ in them. Women delegates successfully lobbied to make the text of these two documents more gender neutral and non-sexist.